Inequities and their determinants in coverage of maternal health services in Burkina Faso - Mwase, Takondwa; Brenner, Stephan; Lohmann, Julia; De Allegri, Manuela (International journal for equity in health, 2018)
Poor and marginalized segments of society often display the worst health status due to limited access to health enhancing interventions. It follows that in order to enhance the health status of entire populations, inequities in access to health care services need to be addressed as an inherent element of any effort targeting Universal Health Coverage. In line with this observation and the need to generate evidence on the equity status quo in sub-Saharan Africa, we assessed the magnitude of the inequities and their determinants in coverage of maternal health services in Burkina Faso.